Postoperative troponin release is associated with major adverse cardiovascular events in the first year after noncardiac surgery. (1st April 2019) - Mol, K.H.J.M.; Hoeks, S.E.; Liem, V.G.B.; Stolker, R.J.; van Lier, F.
Abstract: Introduction: Troponin elevations after intermediate-to-high risk noncardiac surgery are common and can predict mortality. However, the prognostic value for early and late major adverse cardiovascular events (MACE) is less well investigated. The authors evaluated the relationship between postoperative troponin release and MACE in the first year after noncardiac surgery. Methods: This observational cohort registry comprised data of patients aged ≥60 years undergoing intermediate-to-high risk noncardiac surgery between July 2012 and 2015, at the Erasmus University Medical Center, Rotterdam, the Netherlands. High-sensitivity troponin T was measured on day 1 to 3 after surgery. Peak troponin values were divided into four categories: <14 ng·L −1, 14–49 ng·L −1, 50–149 ng·L −1 and ≥150 ng·L −1 . The primary endpoint MACE was defined as the occurrence of myocardial infarction, angina, revascularization therapy or cerebrovascular accident in the first year after surgery. The incidence of MACE and all-cause mortality was calculated using Kaplan-Meier estimates. Cox regression was used to estimate risks for both endpoints. Results: In total, 3085 patients were included for analyses and peak troponin elevation above 14 ng·L −1 was present in 1678 (54.4%) patients. The overall incidence for one-year MACE was 5.8% (3.4%, 6.1%, 10.4% and 40.6% per increasing troponin category) with adjusted HR (95% CI) 1.32 (0.85–2.06), 2.53 (1.42–4.53) and 10.24 (5.91–17.75) for the consecutive increasing categories. One-year mortality occurred in 14.6% and showed a similar stepwise increase with adjusted HR (95% CI) 1.25 (0.98–1.60), 2.39 (1.72–3.32) and 3.79 (2.60–5.54). Conclusion: Our dataset demonstrates a graded relationship between postoperative troponin release and occurrence of MACE in the first year after intermediate-to-high risk noncardiac surgery. Highlights: TnT elevation is known to predict death after surgery. TnT elevation show stepwise increased risks for MACE at 1-year follow-up. TnT elevation after noncardiac surgery is an independent predictor for future MACE. Postoperative TnT could be used in risk stratification for future events.